A global hunger index: measurement concept, ranking of countries, and trends - Wiesmann, Doris (International Food Policy Research Institute, 2006)
Progress in combating hunger and undernutrition has been lagging for decades. Best practices to fight hunger and undernutrition have been available for a long while, but lack of political will among leaders and a lack of political power among the poor have hampered their implementation. Since indices have proven to be powerful tools for advocacy and are able to capture multifaceted phenomena, the Global Hunger Index (GHI) was developed to increase attention to the hunger problem and mobilize the political will to speed up urgently needed progress in the fight against hunger. The GHI captures three dimensions of hunger: insufficient availability of food, shortfalls in the nutritional status of children, and child mortality, which is to a large extent attributable to undernutrition.